The impact of environmental conditions on young entrepreneurs' start-up activities - Blšáková, Daniela; Matuštík, Ondřej; Oškrdal, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
The diploma thesis deals with the influences that affect young people aged 18 to 24 in the establishment of start-ups. The main aim was to find out which environmental factors influence emergence of youth start-ups and how they differ in Europe, China and the US over time. The thesis describes three models that explain the entrepreneurial intentions and that serve better understanding of human behavior in setting up businesses. Further the thesis includes a description of the individual and environmental factors that are based on current studies. Due to the title of thesis only the impact of environmental factors was tested. The analysis was conducted on a public data of the Global Entrepreneurship Monitor.
Vedoucí práce: Ondřej Matuštík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses